Pamenan as an Aesthetic Concept of Creating a Wayang Padang Theatre - Sahrul Nazar (Dance and Theatre Review, 2018)
AbstractWayang Padang Theater performance, perceived from the communication perspective, commonly uses a lapau—a traditional coffeestall (pamenan kato)—style dialogue. Meanwhile, Wisran Hadi also makes use of visual aesthetic (pamenan mato). Pamenan is defined as a game, both creatively or philosophically. Dialogue plays an essential role in the performance that can provide a playful sense that sometimes sounds like there is a misscommunication or an altered meaning. This is actually a distinct characteristic of Wisran Hadi in presenting an entertainment through words. Pamenankato is a technique used by Wisran Hadi in creating a work of art that can entertain the society. The society itself is quite appreciative in absorbing the words uttered by the actors on the stage. On he other side, the visual aesthetic or pamenan matois related with thevisual elements shown on the stage. The aesthetic concept of the play can be seen from the use of words or expressions, the flow of the story, the characters, the costumes, the movements, and the organization of stage, music and lighting. These elements are effectively applied by Wisran Hadi in his Wayang Padang performance.Keywords : pamenan; pamenan Kato; pamenan Mato; Wayang Padang; Wisran HadiAbstrakPamenan sebagai Konsep Estetis Penciptaan Teater Wayang Padang. Pementasan teater Wayang Padang, ditinjau dari segi komunikasi, menggunakan dialog gaya lapau atau warung kopi (pamenan kato). Sementara itu, ditinjau dari segi estetika visual, Wisran Hadi memakai keindahan lihatan (pamenan mato). Pamenan diartikan sebagai permainan, baik permainan secara kreatif maupun permainan secara filosofis. Dialog menjadi hal yang utama dalam pementasan ini. Dialog dalam Wayang Padang seperti bermain-main, kadang-kadang tidak menyambung dan diplesetkan. Hal ini merupakan ciri khas Wisran Hadi dalam menghadirkan hiburan lewat kata-kata. Pamenan kato seperti ini merupakan cara Wisran Hadi dalam membangun karya yang bisa menghibur masyarakat. Masyarakat cukup apresiatif dalam menyimak seluruh kata yang diucapkan oleh aktor di atas pentas. Estetika visual atau pamenan mato berkaitan dengan permainan yang terlihat di panggung pementasan. Estetika konsep penciptaan yang mengarah pada permainan yang terlihat, meliputi unsur kata atau ucapan, cerita, tokoh, kostum, gerak, tata pentas, musik, dan cahaya. Unsur inilah yang dipermainkan oleh Wisran Hadi dalam pementasan teater Wayang Padang.Kata kunci : pamenan; pamenan Kato; pamenan Mato; Wayang Padang; Wisran Hadi